A Review of Raman, Surface-Enhanced Raman Scattering (Sers) and Related Spectroscopic Techniques Applied to Biomolecules in Biomaterials - Garcia-Morgado, M; Garcia-Morgado, M (Sociedad Chilena de Quimica, 2017)
The development of new biomaterials has gained increasing attention in the last decade. One of the most important aspects in the development of these new materials is to understand the chemical cues presents in the native niche. Among all the techniques currently available for measuring those interactions, Raman spectroscopy offers a unique and non-invasive tool for exploring the behavior of the components within a given biomaterial and their surrounding microenvironment. This technique exploits the unique molecular vibrational fingerprints for pinpointing those interactions. The vibrational response can be improved to the single molecule level, in the presence of metal nanoparticles (NPs) with plasmonic properties (silver, gold and copper) in the so-called Surface-Enhanced Raman Scattering (SERS), which can be used for in-situ measurements. Another technique recently developed is the Shell-Isolated Nanoparticle-Enhanced Raman Spectroscopy (SHINERS), which overcomes signal contamination from chemical interactions between biomolecules and the metal surface; it does this by coating the metal surface with an inert layer of alumina or silica. In the present contribution, the role and the applications of Raman, SERS and related spectroscopic techniques in the study of biomolecules in biomaterials are reviewed and discussed.